Recognition and Legalization of Illegitimate Children, and the Legal Consequences, According to the Civil Code and Law no. 1 of 1974 - Nabila Hilmy Khairunnisa Hasibuan; Salwa Khairina Azzahra; Vivian Alyssa Chandra; Nadiatul Maghfirah; Shafa Zhafira Khalid (Jurnal Sahabat ISNU SU, 2024)
In the dynamics of national life, Indonesia, a State of Law, views the supremacy of law as a shared ideal. In this situation, everyone has the right to marry and maintain a legal marriage to have children. Children born out of wedlock are recognized as such because not all children are the result of divorced parents. This study seeks to examine the Civil Code regulations regarding unmarried children, customary law, and the validity of birth certificates of unmarried children. A conceptual approach and normative legal research methodology are used in this study. The primary, secondary, and tertiary legal sources used are then subjected to methodical analysis. The research findings indicate that customary laws, both written and unwritten, are used to regulate illegitimate children because they serve as guidelines for traditional villages in managing their governance. Notarial deeds, birth certificates, certificates issued by civil registration officers, or even the marriage certificate itself may state that the child was born out of wedlock. Because they serve as proof of state recognition of the child's citizenship and civil status, a birth certificate is very important for the child.